2014
DOI: 10.1007/s10584-013-1037-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate change risks to US infrastructure: impacts on roads, bridges, coastal development, and urban drainage

Abstract: Changes in temperature, precipitation, sea level, and coastal storms will likely increase the vulnerability of infrastructure across the United States. Using four models that analyze vulnerability, impacts, and adaptation, this paper estimates impacts to roads, bridges, coastal properties, and urban drainage infrastructure and investigates sensitivity to varying greenhouse gas emission scenarios, climate sensitivities, and global climate models. The results suggest that the impacts of climate change in this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 16 publications
(19 reference statements)
1
70
0
3
Order By: Relevance
“…With the exception of buildings in the 2070 era, which may experience delayed damages from near-surface permafrost thaw because of the lower temperature increase under RCP4.5, mean annual projected damages to all infrastructure types were lower under RCP4.5. These findings are consistent with other studies that have found reduced economic impacts under lower GHG emissions scenarios (35,44).…”
Section: Discussionsupporting
confidence: 93%
“…With the exception of buildings in the 2070 era, which may experience delayed damages from near-surface permafrost thaw because of the lower temperature increase under RCP4.5, mean annual projected damages to all infrastructure types were lower under RCP4.5. These findings are consistent with other studies that have found reduced economic impacts under lower GHG emissions scenarios (35,44).…”
Section: Discussionsupporting
confidence: 93%
“…Under the CIRA framework, these scenarios have been systematically applied to explore different impacts, including water resources, infrastructure, and health. [41][42][43] We examine the effect of climate change and climate policy on U.S. air quality and its associated health risks using the scenarios developed under the CIRA project for consistent analyses of climate impacts. Our modeling framework includes an integrated assessment model, a global atmospheric chemistry model, and a health and economic benefits model.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this section is to illustrate how the different condition monitoring and fault detection methods can be used during the life cycle of the bridge, in order to monitor the evolution of the health state of the bridge over time. A short-span steel bridge is selected due to the fact that short-span bridges are one of the most common structures for railway bridges, and their degradation mechanisms, such as corrosion and cracks, can develop rapidly, once they have been initiated [Chen et al, 1999;AISI, 2007;Psimoulis et al, 2013;Nour et al, 2016;Rocha et al, 2016]. Furthermore, it is worth mentioning that the behaviour of a short-span railway bridge is strongly influenced by the dynamic characteristics of the track and the dynamic properties of the train that is passing over the bridge [Rocha et al, 2012].…”
Section: A Short-span Steel Railway Bridge: a Comparative Studymentioning
confidence: 99%